Synthesis, Spectral Characterization and Antimicrobial Evaluation of Schiff Base Derived From 1-Hydroxy-4-iodo-2-acetonaphthone and 4-Methoxyphenylethylamine - Dhananjay V. Bondar; Vishnu S. Shinde (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Here, we are presented the new Schiff base's synthesis, characterization, and biological properties. The following methods have been used to identify these compounds: FT-IR, 1H and 13C NMR, LCMS, and UV-visible. More than 400 nm peaks in UV-vis. spectra are confirmed, indicating the presence of n→π* and π→π* transitions of non-bonding electrons. The IR measurements confirmed the involvement of azomethine nitrogen and naphthol oxygen in the ligand's bidentate binding. The predicted structures and the Schiff base 1H, 13C NMR spectrum data agreed fairly well. The approved Schiff base ligand was tested for in vitro antibacterial bioactivity against the gram-negative bacteria E. coli, P. aeruginosa, and gram-positive S. aureus, B. subtilis, as well as in vitro antifungal activity against the two fungi C. albicans and A. niger using the agar well diffusion technique. The Schiff base-1-Hydroxy-4-iodo-2-acetonaphthone, which contains halogen, demonstrated moderate to considerable antibacterial activity, suggesting that it could be a suitable lead structure for the creation of novel antimicrobial drugs.
Keywords: Schiff base; 1-Hydroxy-4-iodo-2-acetonaphthone; 4-Methoxyphenylethylamine; antimicrobial